Pelatihan Penggunaan Sistem Inventory Data Barang Pada Gudang CV.Tanaya - Matheus Supriyanto Rumetna; Tirsa Ninia Lina (Journal of Social Responsibility Projects by Higher Education Forum, 2021)
CV. Tanaya is one of the companies engaged in the field of suppliers, this CV buys raw materials in several Agents. The availability of goods is very influential in production planning, therefore inventory data is needed. Goods inventory data processing in the CV. Tanaya is still manual, namely for recording data using a stock card. This raises the motivation to design and conduct training in the use of information systems about inventory data items, especially in the warehouse CV. Tanaya The method used consists of two stages, the first is observation and interviews with the CV. The second stage is to carry out a community education approach, in this case training the use of the system. This aims to make it easier for companies to manage data so that it is faster, accuracy in data processing and improve accuracy in managing the entry and exit of goods stock in the warehouse of CV. Tanaya.